Days of the Bagnold summer [videorecording (DVD)] - Dolan, Monica; Cave, Earl; Brydon, Rob, 1965-; Greig, Tamsin, 1967-; Winterhart, Joff (Greenwich Entertainment, Kino Lorber, 2021)
Sue works in a library; her son Daniel eats chips and listens to Metallica. When his father and stepmother cancel his summer plans to visit them in Florida at the last minute, Sue and Daniel suddenly face the prospect of six long weeks together. An epic war of wills ensues in the unassuming battleground of their suburban home as they each reckon with private tragedies, and pursue their passions.